Duration of Carbapenemase-Producing Enterobacteriaceae Carriage in Hospital Patients - Yin Mo (Emerging Infectious Diseases, 2020)
To determine the duration of carbapenemase-producing Enterobacteriaceae (CPE) carriage, we studied 21 CPE carriers for »1 year. Mean carriage duration was 86 days; probability of decolonization in 1 year was 98.5%, suggesting that CPE-carriers’ status can be reviewed yearly. Prolonged carriage was associated with use of antimicrobial drugs.